Neurobehavioral performance of male methamphetamine-dependent trainees during abstinence in selected narcotic addiction rehabilitation centres, Malaysia - Rahmat @Rahaman, Dzulkhissham (2012)
Methamphetamine (MA) is an illicit psychostimulant drug. Chronic or heavy MA use may induce symptoms resembling paranoid schizophrenia, including delusions, and auditory hallucinations. Excessive use of MA can cause hyperactivity, agitation, and paranoia, and a psychotic state lasting from days to weeks. Methamphetamine abusers not only cope with the negative societal repercussions resulting from abuse, but both the immediate and persistent neurobiological consequences as well. The inexpensive production of MA, its low cost, and long duration of action have made it a very desirable commodity among the drug addict. Methamphetamine can be produce illegally by laboratory with simple instrument needed and experties. Research over the past 10 years has suggested that MA abuse has become a key problem in youth communities. In this study, the Neurobehavioral Core Test Battery (NCTB) was used to evaluate neurobehavioral functions of all tested subjects. This battery included seven sets of tests: Profile of Mood States, Simple Reaction Time,Digit Symbol, Digit Span, Santa-Ana Test, Benton Test, and Pursuit Aiming II. All subjects were interviewed to collect demographic data and information on general health status, and lifestyle. Respondents were selected based on criteria of inclusive and exclusive, and with their voluntary to participate in this study. The respondents are ex-addicts who were placed in rehabilitation center were in abstinence period, Pusat Pemulihan Penagihan Narkotik (PUSPEN) involved with MA, or who has a history of involvement with MA use. In addition, this study is the only male trainees. In this study, the respondents were divided into seven groups; they are: (1) Normal Group, (2) MA addicts that still not undergo Therapeutic Communities (TC), the groups that have undertaking TC program; there are 4 sub-groups in TC program. They are (3) Red which is first level, (4) Yellow as second level, (5) Green as third level and (6) White is the last level. The group was arranged according to trainee’s development in the TC program. The seventh group in this study was the group that consists of PUSPEN trainee that will finish TC program within 2 to 3 weeks. In the study of the Digit Forward Test and Digit Backward Test, there were significant difference (p <0.05) between groups in the Therapeutic Community (White, Green, Yellow and Red). It was showed that, the new trainee (Red) can turn the peg of Santa Ana with same time needed as the trainee that going to finish TC program in the Santa Ana Forward Test. In Santa Ana Backward test, it was showed that there were no significant differences between Yellow, White and Red group. However, Green group showed significant (p<0.05) different with other groups. In the study of the Simple Reaction Test (dominance and non-dominance hand), there were no significant difference between groups in the White, Green, Yellow and Red. This showed that all the groups have same response time. Red Group which is new trainee in TC program was not significantly difference as compared to White Group (final stage of TC). In the study of the Digit Symbol Test, Benton Visual and Pursuit Aiming Test; there were significant difference (p <0.05) among the 7 groups. These showed that perceptual motor speed, learning of associations, ability to organize geometrical pattern in space, memorizing, ability to make quick and accurate movements of trainee are significantly different among the groups. These findings were demonstrated that MA abuse is associated with impairments across a range of neurocognitive domains, including attention/psychomotor speed, learning and memory functioning compared to Normal Group. However, changes can be viewed as a trainee in the TC program where significant difference (p <0.05) can be seen between groups of red, yellow, green and white. The most important factor that cause the differences was believed to be abstinence period that underwent by the trainee. Besides that, there are other factors that cause significant difference in the NCTB test such as duration of addiction, amount of MA taken, and frequency of MA taken. However, the factor of age starting addicted not caused significant difference for all tests among the 7 groups.